Motivational factors affecting the fresh graduates of UiTM Kampus Bandaraya Melaka in choosing private sectors / Nabilah Ismail and Syamimi Waheda Che Seman - Ismail, Nabilah; Che Seman, Syamimi Waheda (Faculty of Business and Management, 2013)
Firstly, the purpose of this research being done is to identify the factors of salary, recognition and fringe benefits that motivate fresh graduates of UiTM Kampus Bandaraya Melaka choosing working in private sector and second objective is to identify the ways to encourage fresh graduates of UiTM Kampus Bandaraya Melaka involve in private sector. Respondents of this research is fresh graduates of UiTM Kampus Bandaraya Melaka.100 of respondents answered the questionnaire. They have given their commitment and cooperation in answering the questionnaire. After questionnaire have been collected, reliability testing is used to determine whether the data are reliable or not to this researcher. Motivational factors affecting the fresh Graduates of UiTM Kampus Bandaraya Melaka in choosing private sector are salary, recognition and fringe benefits. Method that being used in this study is structured questionnaire and all the data collected are being gathered and analyzed by using the Statistical Packages for Social Sciences (SPSS). Thus, for the finding of this research are being presented on Chapter 4 of this report and from there, we can determine either the selected factors give the positive or negative impact towards motivational factors affecting the fresh graduates of UiTM Kampus Bandaraya Melaka in choosing private sector. In chapter 5 is a conclusion and recommendations of this research